IMPLEMENTASI VERTEX GRAPH COLOURING, PARTICLE SWARM OPTIMIZATION, DAN CONSTRAINT BASED REASONING UNTUK UNIVERSITY TIMETABLING PROBLEM (STUDI KASUS: FTI UNTAR) - Josselyn Sinthia Thio; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
An application of exams and courses scheduling is made using Vertex Graph Colouring, Particle Swarm Optimization, and Constraint Based Reasoning method to produce a valid and optimal exam and course schedule which can also fulfill the demands of special schedule and room needs. FTI Untar is used as a study case in this development.  The results of the tests done for the courses scheduling of even semester of 2010 / 2011 till odd semester of 2012 / 2013, without collision of special preferences, show that on average there’s no hard-constraints (constraints that must be satisfied) violation, only 13% of soft-constraints (constaints that are attempted to be satisfied) violations between each course and 6% soft-constraints violation due to the poor preference score of the room or time used.  Whilst, the results of the tests done for the exams scheduling of odd semester of 2011 / 2012 and 2012 / 2013 show that on average there’s no hard-constraint and soft-constraint violation between each course although there is still 1% soft-constraints violation due to the poor preference score of the room used. The development was tested to the Secretariat of Informatics Department in FTI Untar and obtain a positive response because of the user-friendly user interfaces and can help to accelerate the process of course, practicum, and exam schedule’s report making.